Trade Unions and the Tudeh(mass) Party of Iran - Khandagh, Najleh (Advances in Social Sciences Research Journal, 2014)
The Tudeh worked widely amongst the working classes to awaken their class consciousness, encouraging them to fight for their rights by establishing a trade union movement, and urging them to support the Tudeh as the only party concerned for their welfare. Their party platform indeed makes clear how deeply committed to the workers’ cause the Tudeh party actually was, a point illustrated particularly by their concern for female workers, an especially vulnerable group. The fragmentary nature of cottage industry in Iran was harmful to the workers conditions so the Tudeh believed, and they accordingly encouraged the formation of unions, to remove the need for exploiting middlemen between the workers and consumers, giving the employees themselves more control over their work situation 25. Keywords: Tudeh Party, Trade Unions, workers, welfare, conditions, industrial.